Fotobiorreator de iluminação interna para produção de biomassa algal e seus metabólitos - Saadi, Farid Nazih (Universidade Federal de São Carlos, 2018)
Microalgae are organisms with potential applications in the pharmaceutical, food and cosmetic industries due to their ability to produce high added value biomolecules such as fatty acids and volatile compounds. For their physiological development, the algae depend on the availability of carbon dioxide, nutrients and sufficient light for the photosynthetic process to occur. As there is an increase in cell concentration the internal lighting of the algal cultures can be impaired by self-shading. The deficiency in the light supply to the cells can cause a decrease in the physiological yield, affecting the growth and synthesis of the biomolecules. The aim of this study was to develop a new cylindrical photobioreactor with internal LED illumination intermediated by a light intensity controller in order to improve the light availability in all phases and densities of the culture. This would lead to high production of algal biomass and its metabolites that can be used by the various sectors of industry. The system we developed has maximum light incidence of 2775.3 W m-3 and an illuminated area of 0.0314 m2. Defining the BG11 culture medium as the standard for this study, increasing concentrations of this medium (1x, 2x and 10x BG11) were tested in Chlorella sorokiniana cultures. Cellular health was monitored with measures of photosynthetic yield (Phyto-PAM) and the results showed yield of ~ 0.69 in all treatments. This can be considered a confirmation that the physico-chemical conditions provided by the photobioreactor were sufficient to meet the microalgae needs. The cell concentration reported as dry biomass showed that the 1x and 2x BG11 culture media rendered similar biomass, but the 10x BG11 resulted in higher biomass 6.87 g L-1 even though similar cell density (cells per mL) were obtained in comparison with BG1x and 2x. This lead to the interpretation that BG11 10x produced 200% heavier cells than the other treatments and a productivity of 0.36 g L-1 day-1. The system was tested for the growth of Curvastrum pantanale and a picoplankton species, and the results confirmed the versatility of the photobioreactor proposed for the cultivation of other species.
Internally iluminated photobioreactor for production of algae biomass and its metabolites
Keywords: Biomassa; C. sorokiniana; Fotobiorreator; LED; Produtividade; Biomass; Photobioreactor; Productivity; Microalgae; PBR; ENGENHARIAS::ENGENHARIA BIOMEDICA::BIOENGENHARIA::MODELAGEM DE SISTEMAS BIOLOGICOS; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL